PENGARUH KINERJA KEUANGAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2007-2011 - Prayanthi, Ika (JBE (Journal of Business and Economics), 2014)
This study aims to examine whether the financial performance, in this case the Return on Asset and Return on Equity, affect the sustainability reporting. In addition to that, it will also examine whether there is a significant difference on the Return on Asset and the Return on Equity between companies which contrive sustainability reporting and companies which do not. The samples in this study consist of 143 companies, and the data variables are taken from the Indonesian Capital Market Directory and Indonesian Sustainability Reporting Award. This study utilizes the logistic regression and difference testing method. The results from the logistic regression analysis show that there is a significant effect on the Return on Asset towards the sustainability reporting, but no significant effect between the Return on Equity on the sustainability reporting. When it is being tested together, it has been found that only the Return on Asset variable has a significant effect on the sustainability reporting. The result of the difference testing through independent sample T Test indicates that there is a significant difference on both the Return on Asset and the Return on Equity between the companies which contrive sustainability reporting and the companies which do not. The average of the Return on Asset and the Return on Equity of companies which contrive the sustainability reporting is greater compared to the companies which do not contrive the report.